The fight against terrorist recidivism in Russia and China in the global context - N. Korotkikh, Natalya (2018)
In the modern world, the prevention of terrorist attacks is one of the most complicated and relevant challenges facing society. International organizations (NATO, the UN, the Council of Europe, and the Shanghai Cooperation Organization) are actively fighting against terrorism. This study analyzes the fight against terrorism in Russia and China, with regard to global trends. The study involves a comparative analysis of the criminal laws of Russia and China in the field of counterterrorism. The criminal laws of Russia and China do not provide a clear definition of the concept of a terrorist crime. However, this gap is bridged by explanations provided by appropriate authorities and agencies. The study investigates the peculiarities of the establishment of recidivism and special recidivism based on the Criminal Law of the People’s Republic of China and the Criminal Code of the Russian Federation. The study focuses on the understanding terrorist crimes and figuring out the range of concrete actions that are classified as terrorist crimes. The study analyzes changes made to the criminal laws of Russia and China, which enhance responsibility for committing second terrorist offenses.